The Influence of Leadership Style and Organizational Environment on Employee Performance Through OCB - El Rifhiyah, Nabilah (Program Studi Adminsitrasi Pendidikan Universitas Jambi, 2022)
Abstract This study aims to examine the effect of leadership style and organizational climate on employee performance mediated by Organizational Citizenship Behavior (OCB). Primary data sources using a questionnaire taken on the research object of the Bank X with a total sample of 76 respondents. The study uses quantitative descriptive analysis and data processed with SPSS 24 namely regression analysis and path analysis. The results showed that there was a positive influence of leadership style and organizational climate on employee performance. Leadership style and organizational climate influence OCB. OCB mediates leadership style on employee performance and OCB also mediates organizational climate on employee performance. This research recommends that the leaders of Bank X need to review policy on improving the implementation of organizational citizenship behavior (OCB) in order all employees do more productive contribution in the office. Keywords: Employee Performance, Leadership Style, Organizational Climate, Organizational Citizenship Behavior (OCB),